(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Water saturation is an important governing quality and quantity of the hydrocarbon evaluation, as reserve estimation. The challenge of the reservoir engineer is to resolve and understand the differences distribution of water saturation content by using different techniques. However, though out this work illustrate variety models to calculate water saturation which is compared with core measured. Therefore, water saturation is calculated using different models; Archie, Simandoux, Indonesia which are compared with Leverett J-Function (capillary pressure measurements). Archie’s parameters of the studied reservoir rock; Cementation Factor (m) and Saturation Exponent (n) are derived from the log data used. Error of the water saturation estimation may significantly impose bias in the estimation of both quantities. In spite of, there are various factors affecting potential error in water saturation estimation, such as, average permeability, average porosity and Archie’s parameters are used. Consequently, the comparison between results indicates that, Indonesia and Simandoux models are show the smallest average absolute error values, where Archie’s model common one used for water saturation in Carbonate rocks. Three wells are selected to present his comparison.